iotSilo: The Agent Service Platform Supporting Dynamic Behavior Assembly for Resolving the Heterogeneity of IoT - Euihyun Jung; Ilkwon Cho; Sun Moo Kang (International Journal of Distributed Sensor Networks)
Although a lot of researchers have painted a rosy picture of Internet of Things (IoT), there have been no widely accepted solution and related standards until now. To achieve the successful realization of IoT, the close collaboration of devices is the primary requisite. However, the heterogeneity of devices such as different hardware or network connectivity prohibits the realization of IoT. In order to overcome the heterogeneity issue, we suggested the agent service platform named iotSilo in which agents can communicate and cooperate on behalf of their devices. With this delegation approach, the iotSilo can support diverse devices without worrying about their differences. In designing an agent, several software design patterns are adopted to enable the agent to assemble behaviors for hiding the heterogeneity of devices. To investigate the effectiveness of the iotSilo, we developed eleven different types of the IoT devices to emulate real world things with Arduino, deployed the devices in both Korea and Japan, and then conducted three experiments.